TAp73 is essential for germ cell adhesion and maturation in testis - Holembowski, Lena (The Rockefeller University Press, 2014)
A core evolutionary function of the p53 family is to protect the genomic integrity of gametes. However, the role of p73 in the male germ line is unknown. Here, we reveal that TAp73 unexpectedly functions as an adhesion and maturation factor of the seminiferous epithelium orchestrating spermiogenesis. TAp73 knockout (TAp73KO) and p73KO mice, but not ΔNp73KO mice, display a “near-empty seminiferous tubule” phenotype due to massive premature loss of immature germ cells. The cellular basis of this phenotype is defective cell–cell adhesions of developing germ cells to Sertoli nurse cells, with likely secondary degeneration of Sertoli cells, including the blood–testis barrier, which leads to disruption of the adhesive integrity and maturation of the germ epithelium. At the molecular level, TAp73, which is produced in germ cells, controls a coordinated transcriptional program of adhesion- and migration-related proteins including peptidase inhibitors, proteases, receptors, and integrins required for germ–Sertoli cell adhesion and dynamic junctional restructuring. Thus, we propose the testis as a unique organ with strict division of labor among all family members: p63 and p53 safeguard germ line fidelity, whereas TAp73 ensures fertility by enabling sperm maturation.